Environmental Management Accounting and Financial Performance: Green Innovation and Financial Performance as Mediator - Maryati, Sri; Soediro, Achmad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Environmental issues are part of larger corporate plans, involving not only development and expansion but also concern for social responsibility. The inconsistency of results is one of the reasons for further studies to be carried out. This research aims to examine the effect of environmental management accounting which refers to ISO 14001 on company financial performance through green innovation consisting of green product innovation and green process innovation as well as environmental performance as a mediating variable. The population in this study are manufacturing companies registered on the IDX 2020-2023. The sample was selected using the purposive sampling method. The analysis uses e-views 11 with path analysis methods and multiple linear regression analysis. Based on the results, it can be concluded that environmental performance can mediate the relationship between environmental management accounting and financial performance by looking at the influence of the relationship between environmental management accounting and environmental performance, and environmental performance on financial performance. Then the existence of green innovation does not have a role as a link between environmental management accounting and financial performance.